2020
DOI: 10.1186/s40634-020-00279-x
|View full text |Cite
|
Sign up to set email alerts
|

Does the choice of syndesmotic screw versus suture button in ankle surgery has a silver lining? – a technical note

Abstract: Purpose Unstable ankle fractures with associated syndesmotic injury are of considerable morbidity in the professional athlete population. The use of dynamic suture button versus static syndesmotic screws fixation, rehabilitation protocols and timing to return to play are still areas of debate. We report the use of novel algorithm of sequential static and dynamic syndesmotic fixation in an elite football player with Weber C ankle fracture. Methods The patient underwent open reduction and internal fixation for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…In addition, screw syndesmotic fixation alters physical biomechanical movement, which needs additional surgery to remove fixation screws. Therefore, more anatomic methods such as tightrope fixation, suture button fixation, etc., for the syndesmotic fixation were carried out and obtained better clinical outcomes compared with screw syndesmotic fixation ( 9 , 10 , 18 – 20 ). In the other side, recently, the importance of deltoid ligament for the stability of ankle has been identified, and it is believed that repairing injured deltoid ligament at the time of fracture stabilization will obtain better ankle stabilization ( 11 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, screw syndesmotic fixation alters physical biomechanical movement, which needs additional surgery to remove fixation screws. Therefore, more anatomic methods such as tightrope fixation, suture button fixation, etc., for the syndesmotic fixation were carried out and obtained better clinical outcomes compared with screw syndesmotic fixation ( 9 , 10 , 18 – 20 ). In the other side, recently, the importance of deltoid ligament for the stability of ankle has been identified, and it is believed that repairing injured deltoid ligament at the time of fracture stabilization will obtain better ankle stabilization ( 11 , 21 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…For operative treatment of lateral malleolus fracture, open reduction and internal fixation (ORIF) is usually suggested. Syndesmotic fixation was first used to stabilize inferior tibiofibular syndesmosis and recover the tibiotalar contact area (7); however, the high occurrence rate of malreduction of the tibiofibular syndesmosis and the need for an extra procedure for removing syndesmotic screws were observed by surgeons (7)(8)(9)(10). Therefore, deltoid ligament repair was carried out as a more anatomic method to recover the tibiotalar contact area (11).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that it may be useful to first perform an operation with a one-third tubular plate on the fibula and two trans-syndesmotic screws so that the bones can heal properly, with this being replaced at six weeks with a double TightRope to allow full weight-bearing and articulation while avoiding the risk of tibiofibular diastasis and simultaneously allowing the syndesmosis time to repair properly 27 . However, this would inevitably lead to increased costs because of the need for a second surgery 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Además, los pacientes con lesiones sindesmóticas tratados con esta técnica tienen una recuperación funcional y reincorporación al trabajo más rápida y una rehabilitación más corta que los pacientes tratados con tornillos. [14][15][16][17]…”
Section: Discussionunclassified
“…Moreover, patients with syndesmotic injuries treated with this technique experience a faster functional recovery and return to work, as well as shorter periods of rehabilitation, than patients treated with screws. [14][15][16][17]…”
Section: Discussionmentioning
confidence: 99%